Emergence of nontuberculous mycobacteria infections during bedaquiline-containing regimens in multidrug-resistant tuberculosis patients. (November 2020) - Gao, Jingtao; Pei, Yi; Yan, Xiaofeng; Shi, Guomin; Li, Tongxin; Gao, Mengqiu; Liu, Yuhong; Wang, Yufeng; Shu, Wei; Li, Liang; Pang, Yu
Highlights: MDR-TB patients treated with BDQ have experienced sputum culture reconversion due to the emergence of nontuberculous mycobacteria (NTM) infections. The most frequent NTM species is Mycobacterium abscesses. The dramatically rapid development of NTM infections underlines the need for systematic species identification during the follow-up period. Abstract: Objectives: The World Health Organization recommends the use of bedaquiline (BDQ) to formulate efficacious combination regimens against multidrug-resistant tuberculosis (MDR-TB). This study reports, for the first time, a case series of MDR-TB patients treated with BDQ who experienced sputum culture reconversion due to emergence of nontuberculous mycobacteria (NTM) infections. Methods: A multicentre case series was established, including patients who started treatment for laboratory-confirmed MDR-TB between January 1, 2018 and March 31, 2020. The study included patients with positive cultures that had no expression of tuberculosis-specific MPT64 protein. Multilocus sequence analysis was used to perform rapid species identification. Susceptibility to BDQ was detected using Thermo Fisher frozen microtiter plates by the laboratory staff at Beijing Chest Hospital. Results: Among the 286 patients receiving BDQ regimens included in this study, the emergence of NTM isolations was reported in nine cases (3.1%). After exposure to BDQ, seven out of these nine patients achieved culture conversion by 4 weeks. The median time for reported NTM infection was 12 weeks (range: 4–24 weeks). Of these, seven were rapidly growing mycobacteria, and two were slow growing. The most frequent NTM species was M. abscessus (five isolates), followed by M. fortuitum (two isolates), M. avium (one isolate), and M. intracellulare (one isolate). In addition, three patients showed resistance to BDQ at baseline. Conclusion: In conclusion, our results demonstrated the emergence of novel NTM populations in MDR-TB patients during BDQ therapy. The notably rapid development of NTM infections underlines the need for systematic species identification during the follow-up period.